De l’argumentaire anticapitaliste à l’interprétation humaniste : l’évolution de l’enseignement de La Parure de Guy de Maupassant dans l’enseignement du secondaire Chinois et Littérature - Guo Tang (Éducation et Socialisation)
As the first French work chosen in the manual Chinese & Literature, Maupassant’s The Diamond Necklace is a key to understand how Chinese government has tried to impose the image of French literature or society to the young generation. Before, the secondary teachers provided their students a picture of a corrupt capitalist society through the fate of Mathilde. Today, the teachers are no longer satisfied of these old anti-capitalist explanations and try to develop a plural, varied and humanist vision. This article will offer a thorough study of the educational progress of The Diamond Necklace in its complexity and its variation from 1956 to today. This research reflects the causes of the evolution in order to define and explain government’s teaching strategies.